Quantitative Test and Engineering Application of Wear Resistance of a Kind of Mine-Filled Composite Pipeline - Wang, Yong; Yang, Gang-feng; Ma, Cheng-liang; Jia, Quan-li; Jin, Qin-guo (Frontiers in Materials, 2022)
Wear resistance is one of the most important performance indicators of filling pipelines, but there are few studies on its quantitative test and life prediction. In this paper, an experimental device and its application method for testing the wear resistance of the pipeline are proposed, and the device is used to test the wear resistance of the self-developed lining composite pipeline, the traditional 16Mn steel pipeline and the ordinary carbon structural steel pipeline. The results show that the wear resistance of the composite lining material is 12.35 times of that of 16Mn steel and 7.32 times of that of ordinary carbon structural steel. The wear resistance mechanism is analyzed from the perspective of the material composition of the composite liner, mainly because the composite liner material uses fused alumina grain sand, silicon carbide and other extremely wear-resistant materials with high hardness as aggregate, and the aggregates are spherical or nearly spherical particles, with smooth surface and small friction resistance. Finally, through a comparison engineering application of a certain iron ore concentrate transportation. Compared with the traditional 16Mn steel pipeline, the composite lined pipeline has been used for more than 5 years without any problems, while the traditional 16Mn steel pipeline is worn through within 1 year. Engineering application shows that the composite lined pipeline has good wear resistance, and it also confirms the reliability of the detection method proposed in this paper.